Anticarbohydrate antibodies : From molecular basis to clinical application - Müller-Loennies, Sven; Kosma, Paul (Springer Vienna, 2012)
Anticarbohydrate Antibodies - from molecular basis to clinical application compiles current knowledge on the immunological recognition of carbohydrates by the adaptive immune system from a molecular perspective providing fundamental insight needed for advancing clinically relevant diagnostics and therapeutic applications. Based on significant progress in the fields of glycoimmunology and structural biology in recent years, the book comprehensively reviews the state-of-the-art in defining the key elements of carbohydrate recognition by antibodies, the molecular mimicry of carbohydrate epitopes as well as the molecular features leading to specific and relaxed binding modes. Backed-up by a combination of modern technologies to elucidate structural details of carbohydrate-antibody interactions, biomedically important carbohydrate antigens from viral, bacterial, parasite, insect and tumor cells have been analyzed in in-depth reviews written by well-known experts in the field. Fundamental knowledge of these molecular mechanisms eventually provides a rational basis to improve efficacy of carbohydrate-based vaccines and to further refine diagnostic tools in detection of pathogens and malignant cells.